The Efficacy of Percutaneous Patent Foramen Ovale Closure on Migraine: a Meta-Analysis of Randomized Controlled Trials and Observational Studies - Zhang, Quan-Quan; Lu, Jia-Jie; Yan, Man-Yun; Hu, Xiao-Wei; Qin, Yi-Ren; Wang, Da-Peng; Jiang, Jian-Hua; Fang, Qi; Zhao, Hong-Ru (BioMed research international, 2021)
Objectives. Whether patent foramen ovale (PFO) closure is effective on migraine is controversial. This article was aimed at assessing the efficacy of PFO closure on migraine based on randomized controlled trials (RCTs) and observational studies. Methods. We searched PubMed, Embase, and Cochrane databases up to October 2020 evaluating PFO closure versus control in patients with migraine, then conducted a meta-analysis of all RCTs and observational studies, respectively. The main outcomes were (1) respond rate: complete cessation of migraine; (2) reduction in the frequency of migraine attacks per month; and (3) reduction in migraine days per month. Results. Seven studies (3 RCTs and 4 observational studies), containing 887 migraine patients, were identified. (1) The respond rate of PFO closure on migraine was significantly higher than control group both in RCT subgroup and observational studies subgroup (OR 3.86, 95% CI 1.35-11.04, P=0.01 in RCTs; OR 8.28, 95% CI 2.31-29.67, P=0.001 in observational studies). (2) Reduction in frequency of migraine attacks was higher in PFO closure group compared with control group in the RCT subgroup analysis (mean difference MD=0.57, 95% CI 0.23-0.90, P=0.0009). (3) Reduction in migraine days was also higher in PFO closure group compared with control group in the RCT subgroup analysis (MD=1.33, 95% CI 0.35-2.31, P=0.008). Conclusions. PFO closure might be suitable for migraine patients, especially for migraine with aura, by cessation of migraine headaches or reducing migraine attacks and migraine days.